Assessing the relationship between interest rate and reits performance in Malaysia - Ang, Kian Tiong, 1988-, author; Ibrahim @ Atan Sipan, 1963-, supervisor; Fakulti Geoinformasi dan Harta Tanah (2012)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2012